2008
DOI: 10.12968/bjon.2008.17.14.30656
|View full text |Cite
|
Sign up to set email alerts
|

IV therapy: recognizing the differences between infiltration and extravasation

Abstract: Infiltration and extravasation are complications that can occur during intravenous therapy administered via either peripheral or central venous access devices. Both can result in problems with the siting of future venous access devices, nerve damage, infection and tissue necrosis. The nurse is the key to reducing the risk of infiltration and extravasation, through her knowledge and skill in cannulation and the intravenous administration of drugs (by bolus injection or infusion). The nurse must also be able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 13 publications
0
45
1
3
Order By: Relevance
“…It was observed that, in spite of the protocol defined by the institution, the registrations vary regarding application with the occurrence of extravasation of the same drug, as shown below. an extravasation occurs or is suspected, the infusion is stopped and the affected area should be inspected and the treatment given with the correct antidote to the drug (3)(4)6) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that, in spite of the protocol defined by the institution, the registrations vary regarding application with the occurrence of extravasation of the same drug, as shown below. an extravasation occurs or is suspected, the infusion is stopped and the affected area should be inspected and the treatment given with the correct antidote to the drug (3)(4)6) .…”
Section: Resultsmentioning
confidence: 99%
“…Preventive measures are strongly advocated in the the nurse (4,(7)(8) . However, in this study it was not possible to identify preventive measures established by the nursing team in their records, except for the complaints of women during infusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 One of these events is extravasation, caused by the unintentional administration of the chemotherapeutic agent or vesicant solution in the perivascular space or in the subcutaneous tissue, being denominated local dermatological toxicity. 2 As the intravenous route is one of the main routes of administration of the chemotherapeutic agents, extravasation is one of the adverse events that of high incidence. This varies from 0.1 to 6%, however, establishing it, accurately, is difficult, due to underreporting of the occurrence by health professionals.…”
mentioning
confidence: 99%